2016
DOI: 10.1111/adb.12444
|View full text |Cite
|
Sign up to set email alerts
|

Acute naltrexone does not remediate fronto‐striatal disturbances in alcoholic and alcoholic polysubstance‐dependent populations during a monetary incentive delay task

Abstract: There is a concerted research effort to investigate brain mechanisms underlying addiction processes that may predicate the development of new compounds for treating addiction. One target is the brain's opioid system, due to its role in the reinforcing effects of substances of abuse. Substance-dependent populations have increased numbers of the mu opioid receptor (MOR) in fronto-striatal regions that predict drug relapse, and demonstrate disturbances in these regions during the processing of non-drug rewards. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 48 publications
6
31
2
Order By: Relevance
“…Notably, nonsignificant naltrexone effects were found both at the whole-brain voxel-wise level and in ROI analyses of reward processing regions (namely, VS, ACC, and OFC) that have previously been shown to be attenuate with naltrexone during alcohol consumption and cue paradigms (Mann et al, 2014;Myrick et al, 2008;Schacht et al, 2013b;,. These null findings do, however, corroborate and extend previous studies that have failed to observe significant naltrexone-induced changes in VS and in response to alcohol cues (Lukas et al, 2013) or during a monetary incentive delay task (Nestor et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…Notably, nonsignificant naltrexone effects were found both at the whole-brain voxel-wise level and in ROI analyses of reward processing regions (namely, VS, ACC, and OFC) that have previously been shown to be attenuate with naltrexone during alcohol consumption and cue paradigms (Mann et al, 2014;Myrick et al, 2008;Schacht et al, 2013b;,. These null findings do, however, corroborate and extend previous studies that have failed to observe significant naltrexone-induced changes in VS and in response to alcohol cues (Lukas et al, 2013) or during a monetary incentive delay task (Nestor et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…Results from a study of opioid effects on financial decisions (trading game) suggest decreased reinforcement learning after naltrexone (50 mg, n = 62) compared to placebo (n = 116) in healthy participants (Efremidze, Sarraf, Miotto, & Zak, 2017). In contrast to these findings, one study reported no effects of opioid blockade (50 mg naltrexone) on BOLD responses to monetary wins and losses (Monetary Incentive Delay task) in 35 healthy participants (Nestor et al, 2017).…”
Section: Reward-based Decision-makingmentioning
confidence: 93%
“…The insula cortex contains a high number of MORs (Zubieta et al ., ), also making it a target for the modulating effects of naltrexone. We previously reported that the same poly substance group showed a diminished response in the left AIC during acute naltrexone in response to missed rewards on a monetary incentive delay task (Nestor et al ., ), suggesting a blunting of error‐related signalling by naltrexone. The current study, however, suggests an opposing effect of naltrexone in the AIC, possibly by amplifying the detection of no‐go events under the demands of heightened performance monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…For a full description of the cohort used in the current study, please see Nestor et al . (), which examined the same participant groups using a monetary incentive delay task (Nestor et al ., ). In the current study, the AUD group was made up of 21 abstinent alcoholics, with the poly‐SUD group comprised of 25 abstinent alcoholic polysubstance‐dependent individuals (having met criteria for dependence to alcohol plus one or more other substances of dependence).…”
Section: Methodsmentioning
confidence: 99%